2019
DOI: 10.1007/s40333-019-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf gas exchange and photosynthesis curves of Elymus nutans and Potentilla anserina under fencing and grazing conditions in the Qilian Mountains, Northwest China

Abstract: Potentilla anserina L. and Elymus nutans Griseb. are dominant species in the subalpine meadows of China. Grazing is one of the most important factors that influence community structure and productivity of subalpine meadows. Understanding how grazing changes photosynthetic capability is essential for preservation and restoration of grasslands. However, information about the effects of grazing on photosynthetic capability remains inadequate. Experiments were conducted in fencing and grazing areas in the Qilian M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…alpine meadow at the Qilian Mountains significantly increased after enclosure (Liu et al, 2019). In our study, ER of the artificial grassland was the lowest, and a study on Haibei alpine meadow also reported that ER of artificial grassland was lower, which was 1/2-1/3 of the WF grassland and natural grassland, respectively (Zhang Z. et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…alpine meadow at the Qilian Mountains significantly increased after enclosure (Liu et al, 2019). In our study, ER of the artificial grassland was the lowest, and a study on Haibei alpine meadow also reported that ER of artificial grassland was lower, which was 1/2-1/3 of the WF grassland and natural grassland, respectively (Zhang Z. et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…In China, 41.7% of the territory area is covered by grassland. Grassland not only provides abundant meat, milk, fur, and other products, but also has important ecological functions, such as regulating climate, conserving water, and sequestering carbon (Wang and Wang, 2019;Bai et al, 2020). As a sensitive and fragile area to global change, the Qinghai-Tibetan Plateau plays a key role in the regional and global carbon cycle (Yang W. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic parameters of diurnal variation of photosynthesis reflect the continuous ability of material accumulation and physiological metabolism of plants in a day. More importantly, they help when determining and analyzing the limiting factors in photosynthesis (Liu et al, 2019). Our study showed that the diurnal variation of P n in P. heterophylla leaves had an obvious photosynthetic midday depression in the current environmental conditions, when the local temperature had not yet reached a high in mid-May.…”
Section: Discussionmentioning
confidence: 69%
“…Elymus nutans is a kind of perennial gramineous forage, which is widely distributed in the alpine region at an altitude of 3,000-5,000 m (Fu et al, 2014;Liu et al, 2019). It has strong cold resistance and can safely overwinter at low temperature (Ding et al, 2020).…”
Section: Introductionmentioning
confidence: 99%